Epistemologi Filsafat Pendidikan Islam dalam Meningkatkan Pengetahuan Siswa di SMP Muhammadiyah Program Khusus Bayat, Klaten - Mujiburrohman, Mujiburrohman; Nuryahya, Ikhsan (TSAQOFAH, 2025)
Knowledge which is the product of thinking activities is the torch of enlightenment of civilization where humans discover themselves and live life more perfectly. The epistemology of Islamic educational philosophy is a science that studies procedures and the process of obtaining Islamic educational philosophy by studying revelation and phenomena of the universe. The epistemology of Islamic educational philosophy is used to obtain knowledge of Islamic education. This research aims to analyze the epistemology of Islamic educational philosophy in increasing students' knowledge at Muhammadiyah Middle School Bayat Special Program. The epistemology of Islamic educational philosophy focuses on the sources of knowledge and methods used. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with three sources: two male teachers and one female teacher, as well as photo documentation of the interviews. The results of the research show that based on the correct source of guidance, namely the Al-Quran and Hadith, it is then developed with an ongoing curriculum and implementation of teaching with the best methods so as to increase students' knowledge in a focused manner and have character cultivation that meets the target.